2021
DOI: 10.1128/msphere.01140-20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Apoptosis-Related Genes Reveals that Apoptosis Functions in Conidiation and Pathogenesis of Fusarium pseudograminearum

Abstract: Apoptosis, a type of programmed cell death, plays crucial roles in various physiological processes, from development to adaptive responses. Key features of apoptosis have been verified in various fungal microbes but not yet in Fusarium species. Here, we identified 19 apoptosis-related genes in Fusarium pseudograminearum using a genome-wide survey. Expression profile analysis revealed that several apoptosis-related genes were significantly increased during conidiation and infection stages. Among these is FpBIR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Apoptosis, a type of programmed cell death, plays an integral role in plant. It is controlled by cellular oxidative status, hormones, and NDA methylation and plays vital roles in plant development and adaptive responses ( Vanyushin et al, 2004 ; Chen et al, 2021 ). Research has shown that leaf senescence and apoptosis are linked by the downstream of the ethylene trifurcate pathway ( Jin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, a type of programmed cell death, plays an integral role in plant. It is controlled by cellular oxidative status, hormones, and NDA methylation and plays vital roles in plant development and adaptive responses ( Vanyushin et al, 2004 ; Chen et al, 2021 ). Research has shown that leaf senescence and apoptosis are linked by the downstream of the ethylene trifurcate pathway ( Jin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…For F. sacchari transformation, polyethylene glycol-mediated fungal genetic transformation was similar to that for Fusarium pseudograminearum ( 62 ). We constructed a homologous recombination fragment containing flanking sequences of the target gene and hygromycin resistance gene (Hph).…”
Section: Methodsmentioning
confidence: 99%
“…The conserved domains of FpLaeB were predicted via the Conserved Domain Search Service (CD Search) in the National Center for Biotechnology Information (NCBI). The phylogenetic tree of FpLaeB and its homology proteins were constructed via the neighbour-joining method with the MEGA version 7.02 software package (Xia et al, 2021).…”
Section: Fplaeb Gene Deletion and Complementaritymentioning
confidence: 99%